Formy kształcenia elitarnego na poziomie wyższym w Polsce = Elite form of higher education in Poland - Kola, Anna Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the problem of elite form of higher education in Poland, namely: doctoral studies, fine art studies and MBA studies realized most often in the cooperation with foreign universities and schools of public administration. They serve different functions to the society and set themselves tasks which are not realized by other educational institutions.
Keywords: szkolnictwo wyższe; elitarność; elita; Polska